2017
DOI: 10.5194/bg-14-3859-2017
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the partial pressure of carbon dioxide in the Mauritanian–Cap Vert upwelling region between 2005 and 2012

Abstract: Abstract. Coastal upwellings along the eastern margins of major ocean basins represent regions of large ecological and economic importance due to the high biological productivity. The role of these regions for the global carbon cycle makes them essential in addressing climate change. The physical forcing of upwelling processes that favor production in these areas are already being affected by global warming, which will modify the intensity of upwelling and, consequently, the carbon dioxide cycle. Here, we pres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…The Gulf of Cádiz acts as a source of CO 2 to the atmosphere during the months of summer (ST2, ST6) and autumn (ST3, ST7) and as a sink in spring (ST1, ST5) and winter (ST4, ST8). Previous studies conducted in the Gulf of Cádiz are consistent with the behaviour found in this study (González-Dávila et al, 2003;Aït-Ameur and Goyet, 2006;Ribas-Ribas et al, 2011).…”
Section: Ocean-atmosphere Co 2 Exchangesupporting
confidence: 93%
See 2 more Smart Citations
“…The Gulf of Cádiz acts as a source of CO 2 to the atmosphere during the months of summer (ST2, ST6) and autumn (ST3, ST7) and as a sink in spring (ST1, ST5) and winter (ST4, ST8). Previous studies conducted in the Gulf of Cádiz are consistent with the behaviour found in this study (González-Dávila et al, 2003;Aït-Ameur and Goyet, 2006;Ribas-Ribas et al, 2011).…”
Section: Ocean-atmosphere Co 2 Exchangesupporting
confidence: 93%
“…With the total surface of the study area (52.8 × 10 2 km 2 ) and the mean annual flux during the eight cruises, the uptake capacity estimated for the Gulf of Cádiz will be 4.1 Gg C yr −1 . The findings of previous studies carried out in the Gulf of Cádiz coincide with the behaviour observed in this study (Santana-Casiano et al, 2002;González-Dávila et al, 2003;Huertas et al, 2006;de la Paz et al, 2009;Ribas-Ribas et al, 2011), with the exception of the study by Aït-Ameur and Goyet (2006) in which it was estimated that the Gulf of Cádiz acts as a source of CO 2 to the atmosphere, although that study only corresponds to the summer season.…”
Section: Ocean-atmosphere Co 2 Exchangesupporting
confidence: 89%
See 1 more Smart Citation
“…This input of colder waters, with greater loading of nutrients and higher concentrations of CO2 (e.g. Liu et al, 2010;Xue et al, 2015;González-Dávila et al, 2017) can affect the distributions of pCO2 found in the Gulf of Cádiz.…”
Section: General Trendsmentioning
confidence: 99%
“…Unattended measurements referenced against compressed air standards traceable to atmospheric CO 2 standards are now done routinely on ships and, since the 2000s, on moorings (Sutton et al, 2014). The measurements cover much of the global ocean, and allow regular access to regions of economic and environmental importance such as upwelling regions (González-Dávila et al, 2017). Many of the measurements are performed following standard operating procedures (e.g., Pierrot et al, 2009) and much of the data are submitted to global datasets and undergo independent secondary quality control.…”
Section: Introductionmentioning
confidence: 99%